Respostas

2013-12-05T00:18:32-02:00
A) x - 2y = 0 x = 2y
------------
x² - y² = 27
4y² - y² = 27
3y² = 27
y² = 9
y = 3
x = 2y = 2*3 = 6
----------------------------------------------------
x = 4y
y² - 2x = 9
y² - 2*4y = 9
y² - 8y - 9 = 0
y' = -9
y'' = 1
Até mais !
2013-12-05T00:21:58-02:00
A) x - 2y = 0
   x² - y² = 27

x = 2y

2y² - y² = 27
 y² = 27
y = V27
y = 5,2  aproximadamente

x = 2 . 5,2 = 10,4  aproximadamente


b) x = 4y
     y² - 2x = 9

y² - 2 . 4y = 9
y² - 8y = 9
y² - 8y - 9 = 0

a= 1
b= -8
c= -9

x = -( -8) + - V -8² - 4 . 1 . - 9/2 . 1
x = 8 + - V 64 + 36 / 2
x = 8 + - V 100 / 2
x = 8 + - 10/2
x'= 8 + 10 / 2 = 18/ 2 = 9
x"= 8 - 10 / 2 = - 2/2 = - 1